Enantioselective aza-Friedel–Crafts reaction of furan with α-ketimino esters induced by a conjugated double hydrogen bond network of chiral bis(phosphoric acid) catalysts. Issue 30 (28th June 2018) - Hatano, Manabu; Okamoto, Haruka; Kawakami, Taro; Toh, Kohei; Nakatsuji, Hidefumi; Sakakura, Akira; Ishihara, Kazuaki
Abstract : Chiral C 2 - and C 1 -symmetric BINOL-derived bis(phosphoric acid) catalysts facilitated the enantioselective aza-Friedel–Crafts reaction of 2-methoxyfuran with α-ketimino esters. Abstract : Chiral C 2 - and C 1 -symmetric BINOL-derived bis(phosphoric acid) catalysts, which have OP(O)(OH)2 /OP(O)(OH)(OR) moieties at the 2, 2′-positions, were developed and used for the enantioselective aza-Friedel–Crafts reaction of 2-methoxyfuran with α-ketimino esters for the first time. The intramolecular conjugated double hydrogen bond network is a key to increasing the Brønsted acidity and preventing deactivation of the catalysts. Highly functionalized α-amino acid derivatives with a chiral quaternary carbon center could be transformed into versatile optically active N - and O -heterocycles and an α-aryl-substituted serine.